2007
DOI: 10.1029/2006gb002730
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of organic nitrogen from headwater streams to large rivers across the conterminous United States

Abstract: [1] The frequency and magnitude of hypoxic areas in coastal waterbodies are increasing across the globe, partially in response to the increase in nitrogen delivery from the landscape (Diaz, 2001;Rabalais et al., 2002). Although studies of annual total nitrogen and nitrate yields have greatly improved understanding of the contaminant sources that contribute to riverine nitrogen loads (Alexander et al., 2000;Caraco and Cole, 1999), the emphasis of these studies on annual timescales and selected nitrogen forms is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
46
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 42 publications
7
46
0
Order By: Relevance
“…Previous studies in temperate forested catchments in south America, where anthropogenic inputs are very low, have shown a relatively high proportion of DON in streams (Perakis and Hedin, 2002). DON has also been found to be an abundant form of dissolved N in streams across a range of catchments in the US (Scott et al, 2007). This study has shown DON it to be the most abundant form of dissolved N in groundwaters and streams in an upland moorland catchment of relatively low permeability with comparatively high depositional sources of anthropogenic N. DON concentrations in the shallow groundwater system showed similar seasonal trends to those in the Gwy and the Cerrig.…”
Section: Spatial and Temporal Variations In Nitrogen Chemistrymentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies in temperate forested catchments in south America, where anthropogenic inputs are very low, have shown a relatively high proportion of DON in streams (Perakis and Hedin, 2002). DON has also been found to be an abundant form of dissolved N in streams across a range of catchments in the US (Scott et al, 2007). This study has shown DON it to be the most abundant form of dissolved N in groundwaters and streams in an upland moorland catchment of relatively low permeability with comparatively high depositional sources of anthropogenic N. DON concentrations in the shallow groundwater system showed similar seasonal trends to those in the Gwy and the Cerrig.…”
Section: Spatial and Temporal Variations In Nitrogen Chemistrymentioning
confidence: 94%
“…The detrimental effects of nitrogen deposition on surface water chemistry have been widely reported both in Europe and North America (Evans and Monteith, 2001;Stoddard, 1994), however recent improvements caused by emission targets have occurred (Skjelkvale et al, 2005). While most studies have focussed on the effect of dissolved inorganic nitrogen (DIN) in terms of nitrogen cycling and water quality, the role of dissolved organic nitrogen (DON) in nitrogen cycling and bioavailability has also been shown to be important in a range of environments (Scott et al, 2007;Seitzinger et al, 2005;Jones et al, 2004;Willett et al, 2004;Seitzinger and Sanders, 1997;Carlsson and Graneli, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Dissolved organic nitrogen (DON) generally represents a large fraction of the total dissolved nitrogen (N) pool in relatively unpolluted streams (Lewis et al 1999;Perakis and Hedin 2002), and total organic N (including particulate N) dominates N flux in large rivers across North America (Scott et al 2007). Agriculture and urban land uses often increase DON concentrations and bioavailability in streams across the United States (Pellerin et al 2006), although this increase is generally lower than the drastic increases in inorganic N (Stanley and Maxted 2008).…”
mentioning
confidence: 99%
“…Therefore, DBC and other DOM components can be used to assess how basin characteristics, such as land use and wildfire activity, can impact fluvial health (Degens et al, 1991;Richey et al, 2004). While it has been well-established that anthropogenic activities increase nutrient export to inland surface waters (Scott et al, 2007;Wilson and Xenopoulos, 2009;Mattson et al, 2009), it is not yet known how humans may impact the composition of the DBC pool via processes such as urbanization and agricultural development. Wildfires are ubiquitous across landscapes (Korontzi et al, 2006) and can significantly alter the geomorphology and hydrology of watersheds in which they occur (Shakesby and Doerr, 2006 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…10 It has been well established that human activities influence the composition of DOM and increase the proportion of nutrients exported to inland surface waters. [11][12][13] The enrichment of organic nutrients, such as N, S, and P, can alter DOM reactivity and sorption processes 14 or trigger autochthonous production of relatively labile DOM. 15,16 As such, the conversion of natural vegetation landscapes to agricultural fields has been strongly linked to increased contributions of dissolved organic N (DON) to in-stream DOM.…”
Section: Introductionmentioning
confidence: 99%